The politics of human rights in East Asia - Christie, Kenneth; Roy, Denny, 1960- (London ; Sterling, Va. : Pluto Press, 2001)
Refugees fleeing East Timor. Tiananmen Square in China. The killing fields in Cambodia. Freedom of speech in Singapore. The subject of human rights in Asia is a hotly debated one. In The Politics of Human Rights in East Asia, the authors survey the human rights records and attitudes of each country. The countries covered are: China, Taiwan, Korea, Japan, Indonesia, Myanmar, Cambodia, Vietnam, Thailand, the Philippines, Malaysia and Singapore. Kenneth Christie covers Southeast Asia and Denny Roy covers Northeast Asia. They conclude with a discussion of the Association of East Asian Nation's (ASEAN) role and suggestions for the future. Throughout, they examine the competing meaning of human rights in the Western versus the non-Western context and place the role of human rights within the framework of each country's history and political and economic development.
Introduction: Human Rights in East Asia -- Southeast Asia / Kenneth Christie -- Malaysia, Singapore and ASEAN -- Myanmar and Vietnam -- Indonesia -- Thailand and the Philippines -- Cambodia -- Northeast Asia / Denny Roy -- China -- North and South Korea -- Japan.
Includes bibliographical references (pages 277-302) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Human rights -- East Asia; Human rights -- Southeast Asia; Droits de l'homme (Droit international) -- Asie du Sud-Est.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; POLITICAL SCIENCE -- Human Rights; Human rights; East Asia; Southeast Asia; Menschenrechtspolitik; Ostasien; Südostasien; Mensenrechten; Oost-Azië